2018
DOI: 10.1080/08941939.2018.1424272
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lidocaine and Atropine on Fentanyl-Induced Cough: A Randomized Controlled Study

Abstract: We determined that premedication with atropine suppressed the incidence and severity of fentanyl-induced cough during induction of general anesthesia. We think that, due to its antimuscarinic effect, atropine is as effective as lidocaine as a premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…These receptors are irritated by opioids; thus, tracheal smooth muscle is stimulated to be constricted [20]. Sufentanil-induced histamine release from lung mast cells [19]or supraglottic obstruction by soft tissue [21,22] represent other likely mechanisms of cough. A study demonstrated that the closure of the vocal cord after injecting sufentanil may be the major mechanism of cough [23].…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are irritated by opioids; thus, tracheal smooth muscle is stimulated to be constricted [20]. Sufentanil-induced histamine release from lung mast cells [19]or supraglottic obstruction by soft tissue [21,22] represent other likely mechanisms of cough. A study demonstrated that the closure of the vocal cord after injecting sufentanil may be the major mechanism of cough [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis is controversial, some studies have found that pre-administration of anticholinergic drugs such as atropine cannot reduce the incidence of FIC ( Lui et al, 1996 ). While resent study showed that atropine administered in the preoperative period is as effective as lidocaine in preventing FIC ( Naldan et al, 2019 ).…”
Section: Mechanism Of Fentanyl-induced Coughmentioning
confidence: 99%
“…Numerous pharmacological or non-pharmacological measures have been taken to prevent OIC. Therein, nonpharmacological measures are characterized by diluting drug concentration, slowing down injection rate, using the peripheral injection site, reducing the drug dose, instructing patients on performing the huffing maneuver, and verifying the proper administration sequence of the drug (Ambesh et al, 2010;Min et al, 2012;Shrestha et al, 2012;Xiong et al, 2020). Currently, pharmacological interventions have been widely used in the clinical setting, including lidocaine, dezocine, dexmedetomidine, ketamine, and butorphanol (Shuying et al, 2016;Zhang et al, 2018;Clivio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%